«POLITICAL COMPRADOR» AS A PHENOMENON IN THE PROCESS OF GLOBALIZATION - Шаповаленко, М. В. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2021)
The main factors of the comprador phenomenon as an actor of globalization are analyzed. The global liberal democracy that took shape during the second half of the 20th century is now being transformed. New actors are entering on the geopolitical space. Geopolitical order in the first decades of the XX s. faces the challenges of both the past century and the new. The issues of the new agenda and factors of new challenges are highlighted; shows the prospects for overcoming geopolitical turbulence. Attention is focused on the intensification of the challenges of the 20th century. along with the emergence of new ones in the second decade of the twenty-first century. Among these challenges - the Covid-19 pandemic and, accordingly, the global quarantine, which led to an increase in social tension in societies of different regions of the world, put on question the ability of state structures to ensure national security and the health of their citizens, which in general can have unexpected consequences, both for individual regions and countries, and the world as a whole. Due to the closure of state borders, the curtailment of transport links between continents and countries, between the internal national regions, a situation that is atypical for a globalized world has been created, which is familiar to us from the historical past, namely, the recreation of the world of fragmented feudalism, where other mechanisms of social and political interaction operate. It is indicated that from the point of view of the world-systems analysis, a small number of them belong to the capitalist center, that is, to the core, where the global agenda and the methods of protecting national security are formed. But the overwhelming majority of countries and states are in the periphery and semi-periphery groups. The phenomenon, which was the result of the colonial policy of nascent capitalism, persists to this day, but in other forms, retaining its functions. At the same time, the need to support the neo-colonial order remains, and therefore there is still a political interest in the formation of such groups in the third world (periphery) countries.